Mapping the Bruneian and Acehnese reponses towards sharia law formalization and its implementation - Salleh, Abdu Muizz Mohd; Widigdo, Mohammad Syifa Amin (Universitas Ahmad Dahlan, 2024)
Brunei Darussalam and Aceh are the only two Southeast Asian regions that apply Islamic Sharia law. Both regions have applied Islamic Sharia law for more than ten years and yet have received many reactions from both internal and external regarding the application. This study aims to examine the formulation of sharia in Brunei and Aceh and how the people of Brunei and Aceh respond to its implementation. Based on the findings, Shari law in Aceh hudud tends to appear more liberal and moderate because the ideas are not connected to a school of fiqh. At the same time, Brunei demonstrates a distinct